ТОҒ ЖИНСЛАРНИНГ ЛИТОЛОГИК, ПЕТРОГРАФИК ВА ФИЗИК-МЕХАНИК ХОССА ВА ХУСУСИЯТЛАРИНИ ТАҲЛИЛ ҚИЛИШ (САРИКЎЛ ВА ХОДЖАДИК КОНЛАРИ МИСОЛИДА) - Қурбонов, Элбой; Ашуров, Олим; Абдурахманов, Ботир; Исомиддинов, Ёқуб (Innovatsion texnologiyalar, 2022)
The article studies the structure-texture, lithological composition of rocks in Sarikul and Khodjadik deposits, evaluates the physical and mechanical properties and properties of rocks and provides a scientific basis. Rocks are divided into classifications according to the degree of strength, depending on changes in physical and mechanical properties and properties.